STRATEGI IMPLEMENTASI MOTIF BATIK KHAS SANGIRAN SEBAGAI UPAYA PELESTARIAN SITUS SANGIRAN: THE IMPLEMENTATION STRATEGY OF BATIK PATTERNS FROM SANGIRAN AS A WAY TO PRESERVE THE SANGIRAN SITE - Hermanto, Wiwit (BBPPMPV Seni dan Budaya Yogyakarta, 2024)
In 1996, UNESCO gives recognition to Sangiran as the Cultural World Heritage because of the importance contribution in knowledge such as the finding of human fossil, soil layers, artifacts, and fossil of fauna. Beside archaeology potential, the societies who live there also have cultural potential such as knowledge and traditional technology, natural resources and vegetation. The potential encourage BPSMP Sangiran to do a revitalization of batik pattern in order to highlight the importance value of Sangiran Site. Through batik pattern from Sangiran, it becomes a part of 2 preservation of Cultural World Heritage; they are tangible heritage and intangible heritage. The purpose of revitalizing batik from sangiran is to raise the characteristics of this site, provide benefits for the society, as a means of education, socialization, and invite them to participate in preserving the Sangiran Site. Batik pattern from Sangiran can be a way to preserve the Sangiran site which can be carried out and developed, mass production, exclusive marketing, support and participation of the government and non-government parties. There are many challenges to develop, and the writer gives solution to answer it. Tahun 1996 UNESCO memberikan pengakuan pada Situs Sangiran sebagai Warisan Budaya Dunia karena kontribusi penting dari situs ini berupa temuan fosil manusia, perlapisan tanah, artefak, dan fosil fauna. Selain potensi arkeologi, masyarakat yang mendiami situs ini memiliki potensi budaya berupa pengetahuan dan teknologi tradisional, kekayaan alam, dan vegetasi. Potensi tersebut mendorong Balai Pelestarian Situs Manusia Purba (BPSMP) Sangiran untuk melakukan revitalisasi dengan menyasar motif batik guna mengangkat nilai penting Situs Sangiran. Melalui motif batik khas Sangiran, menjadi bagian pekerjaan pelestarian 2 Warisan Budaya Dunia Indonesia yang telah diakui dunia, yaitu pelestarian budaya bendawi (tangible heritage) dan non bendawi (intangible heritage). Tujuan revitalisasi motif batik adalah untuk mengangkat ciri khas yang ada pada situs ini, sarana edukasi, sosialisasi, serta mengajak masyarakat berperan melestarikan Situs Sangiran. Pengembangan motif batik khas Sangiran dapat sebagai salah satu upaya pelestarian Situs Sangiran ke depan akan menemui berbagai tantangan. Solusi yang diberikan dalam menjawab tantangan berupa pengajuan hak cipta, melakukan produksi massal, merencanakan pemasaran yang tepat, dan pengembangan motif batik khas Sangiran.